Impact of Capital Adequacy on Banks’ Performance: Considering the Basel International Regulatory Framework for Banks (ETIKONOMI, 2021)
This study examines the impact of banks' capital on the performance of banks. The studies adopted a fixed-effect model estimation. Time-series data covering the period 2008-2017 for Ghanaian listed universal banks was considered. We found out that the bank’s capital and banks’ net profit after tax has a positive and significant relationship with banks’ total asset base as a performance indicator. We further discovered through correlational analysis that there is a strong negative link between banks' outstanding loans (credit advancement) and banks' performance. The fundamental implications of this study are to encourage the monitoring of capital adequacy of banks since it creates opportunities for banks to perform effectively.JEL Classification: E5, E44, G21, G30How to Cite:Atuahene, S. A., Yusheng, K., Bentum-Micah, G., & Aboagye, A. K. (2021). Impact of Capital Adequacy on Banks’ Performance: Considering the Basel International Regulatory Framework for Banks. Etikonomi: Jurnal Ekonomi, 20(1), 45 – 54. https://doi.org/10.15408/etk.v20i1.15590.